Papel da alfa-sinucleína associada à Doença de Parkinson - Ana Carolina Greis Antunes (2020)
Parkinson's disease is a progressive neurological disease, where there is loss of dopaminergic neurons, primarily in the substantia nigra in its compact portion and by the presence of Lewy bodies, aggregates composed mainly of alpha-synuclein and ubiquitin proteins. It is possible to verify dopamine depletion in the projection area of the neurons, being considered the main cause of parkinsonism. This disease has no cure and involves genetic and environmental factors, which trigger motor and non-motor alterations capable of resembling other diseases, making medical diagnosis difficult. The deposition of protein clusters known as Lewy bodies and Lewy neurites, which occur within the neurons in the brain, characterize histopathologically the PD. In certain circumstances, such as duplication, gene mutation, increased protein concentration or presence of specific ligands, α-Syn may undergo conformational changes, where its structure will form toxic aggregates and amyloid plaques with greater resistance to proteolytic degradation and fibrillar appearance . It is a literature review of a descriptive nature, where the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO) and International Literature on Health Science ( MEDLINE) / PUBMED. The inclusion criteria were: articles made available in full, dated between 2000 and 2019, in English and / or Portuguese languages. At the end of this study it can be concluded that, if α-Syn oligomeric species are the main cause of PD toxicity, there is a need for investments for new research and understanding regarding the conformations of alpha-synuclein protein elucidating its characteristics, since it can change according to the physiological environment in which it is inserted.